COVID‐19 outcomes in haematopoietic cell transplant recipients: A systematic review and meta‐analysis. Issue 3 (14th June 2022) - Lim, Yeong Jer; Khan, Umair; Karpha, Indrani; Ross, Andrew; Saif, Muhammad; Remberger, Mats; Kalakonda, Nagesh; Pettitt, Andrew R.; Floisand, Yngvar
Abstract: Up‐to‐date information on coronavirus disease 2019 (COVID‐19) outcomes and risk factors in haematopoietic cell transplantation (HCT) recipients is required to inform on decisions about cancer treatment and COVID‐19 mitigation strategies. We performed a meta‐analysis to address this knowledge gap. All studies with at least five patients who reported COVID‐19‐related deaths in HCT recipients were included. The primary outcome was COVID‐19‐related death. Secondary outcomes were COVID‐19‐related mechanical ventilation (MV) and intensive care unit (ITU) admission. The cumulative COVID‐19‐related death rate among HCT recipients was 21% (95% confidence interval [CI] 18%–24%), while MV and ITU admission rates were 14% (95% CI 11%–17%) and 18% (95% CI 14%–22%), respectively. Subgroup analysis showed higher death rates in patients who developed COVID‐19 within 12 months of HCT (risk ratio [RR] 1.82, 95% CI 1.09–3.03), within 6 months of receiving immunosuppressant drugs (RR 2.11, 95% CI 1.38–3.20) or in the context of active graft‐versus‐host disease (RR 2.38, 95% CI 1.10–5.16). Our findings support the idea that HCT should remain an integral part of cancer treatment during the COVID‐19 pandemic but also highlight the need to prioritise preventative measures in those patients who are at increased risk of adverse COVID‐19 outcomes.